Asymmetries in the Coordinated Direct Investment Survey : What Lies Behind? - Angulo, Emma.; Hierro, Alicia (Washington, D.C. : International Monetary Fund, 2017)
This paper analyzes asymmetries in direct investment positions reported in the Coordinated Direct Investment Survey (CDIS) following a top down approach. First, it examines asymmetries at global level; second, it examines asymmetries between CDIS reported and derived data for individual economies; and third, the paper analyzes data at bilateral economy level. Then, the paper explores seven main reasons for asymmetries, including those arising even when economies follow international standards. Finally, the paper includes a section on addressing bilateral asymmetries and concludes with specific planned actions to reduce asymmetries, including initiatives led by international organizations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet